IMPACT OF MARKETING, SOCIO-ECONOMIC AND CULTURAL VARIABLES ON CONSUMER CHOICE OF HEALTH INSURANCE (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
In an econometric framework, the present study  is an examination of the relationship between  the consumers’ choice for health insurance  and its determinants. The Structural Model  assessment has been employed to study the  impact of Marketing Variables, Socio-Economic  Variables and Cultural values on Consumer  Choice in Health Insurance segment. The results  have found to be statistically significant which  shows that there is impact of Socio-Economic  Variables, Marketing Variables, and Cultural  values on Consumer Choice.
Keywords: Marketing Variables; Socio-Economic Variables; Cultural Variables; Consumer Choice; Health Insurance